Rfoot‐seq: Transcriptomic RNase Footprinting for Mapping Stable RNA‐Protein Complexes and Rapid Ribosome Profiling. Issue 4 (25th April 2023) - Li, Qianru; Stroup, Emily K.; Ji, Zhe
Abstract: Ribosome profiling isolates ribosome‐protected fragments for sequencing and is a valuable method for studying different aspects of RNA translation. However, conventional protocols require millions of input cells and time‐consuming steps to isolate translating ribosome complexes using ultracentrifugation or immunoprecipitation. These limitations have prevented their application to rare physiological samples. To address these technical barriers, we developed an RNase footprinting approach named Rfoot‐seq to map stable transcriptomic RNA‐protein complexes that allows rapid ribosome profiling using low‐input samples (Li, Yang, Stroup, Wang, & Ji, 2022). In this assay, we treat a cell lysate with concentrated RNase without complex crosslinking and retained only RNA footprints associated with stable complexes for sequencing. The footprints in coding regions represent ribosome‐protected fragments and can be used to study cytosolic and mitochondrial translation simultaneously. Rfoot‐seq achieves comparable results to conventional ribosome profiling to quantify ribosome occupancy and works robustly for various cultured cells and primary tissue samples. Moreover, Rfoot‐seq maps RNA fragments associated with stable non‐ribosomal RNA‐protein complexes in noncoding domains of small noncoding RNAs and some long noncoding RNAs. Taken together, Rfoot‐seq opens an avenue to quantify transcriptomic translation and characterize functional noncoding RNA domains using low‐input samples. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Harvesting and lysing adherent cells Alternate Protocol 1 : Harvesting and lysing suspension cells Alternate Protocol 2 : Harvesting and lysing primary tissue samples Basic Protocol 2 : RNase treatment and footprint purification for low‐input samples Alternate Protocol 3 : RNase treatment and footprint purification for ultra‐low‐input samples Basic Protocol 3 : Library preparation for high‐throughput sequencing Support Protocol : Preparation of dsDNA markers for library size selection Basic Protocol 4 : Data analysis and quality control after sequencing